Potassium Persulfate Mediated Oxidative Radical Cyclization of 1,3-Dicarbonyl Compounds with Styrenes for the Synthesis of Dihydrofurans - Wang, Shun; He, Lin-Ye; Guo, Li-Na (Synthesis, 2015)
A potassium persulfate promoted tandem radical addition/cyclization of 1,3-dicarbonyl compounds with styrenes has been developed. This transition-metal-free procedure provides an efficient approach to a diverse set of substituted dihydrofurans in moderate to good yields.
Keywords: dicarbonyl compounds; styrenes; free radicals; cyclizations; tandem reactions; furans